A Brief Analysis of the Influencing Factors and Practical Application of Educational Reform in Rural Revitalization -- Taking Rural Women's Political Participation as an Example - ShuShu, Tan; Lucy, Sebli-Seidelson (UK Zhende Publishing Limited, 2022)
Empowering rural women through political participation and educational reform is not only key to revitalizing rural communities, but also unlocking a powerful force for positive change that has been long overlooked. This study aims to investigate the impact of educational reforms and rural revitalization on rural women's political participation barriers in five villages of Guiyang city, China. The research used a quantitative method, and 303 responses were collected. The study found that all of the hypotheses were accepted, except the moderation hypothesis. The study found that educational reforms have a significant impact on rural women's political participation barriers. The findings also indicated that rural revitalization significantly affects rural women's political participation barriers and acts as a mediator and moderator in the relationship between educational reforms and rural women's political participation barriers. The study used a PLS-SEM method to analyze the data, and the independent variable "educational reform" was divided into three sub-variables: education, personal, and governmental. The dependent variable "rural women's political participation barriers" was also divided into three sub-variables: social-cultural barriers, institutional barriers, and barriers related to tools, capacities, and resources. The results of this study have significant implications for policymakers and researchers in the field of rural development and women's political participation. The study highlights the need for continued efforts to improve educational reforms and rural revitalization programs to promote rural women's political participation.